2018
DOI: 10.1152/physiolgenomics.00042.2018
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction shortens cardiac telomere length, but this is attenuated by exercise in early life

Abstract: Growth restriction shortens cardiac telomere length, reflecting the cardiac pathologies associated with low birth weight. Exercise in early life may offer long-term protective effects on cardiac telomere length which could help prevent CVD in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Preclinical studies can be a guide to explain the reasons for this condition. Boot et al caused growth retardation in rats by creating a uteroplacental insufficiency, and they found that short ening occurred in the cardiac TL of these rats and that this deteri oration was prevented by exercise, which also increased heart weight [36]. In other words, cellular aging that starts in intrauter ine life may prepare the ground for future diseases [37].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies can be a guide to explain the reasons for this condition. Boot et al caused growth retardation in rats by creating a uteroplacental insufficiency, and they found that short ening occurred in the cardiac TL of these rats and that this deteri oration was prevented by exercise, which also increased heart weight [36]. In other words, cellular aging that starts in intrauter ine life may prepare the ground for future diseases [37].…”
Section: Discussionmentioning
confidence: 99%